Budaya Takzim Santri kepada Kyai sebagai Pendidikan Adab: Studi Etnografi di Pondok Pesantren Nurul Hidayah Fil Jabal Bogor - Tita Hasanah; Ratna Triani Suhendar; Sapari (JURNAL KAJIAN ISLAM MODERN, 2026)
This study aims to describe and analyze the culture of respect for Kyai among students as a form of adab education at the Nurul Hidayah Fil Jabal Islamic Boarding School in Bogor Regency. The study used a qualitative approach with an ethnographic design to understand the practice of the culture of respect from the perspectives of Islamic boarding school cultural actors. The research informants consisted of a Kyai, a Ustadzah, a senior student, and a new student who were selected purposively. Data were obtained through participant observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of data reduction, categorization, data presentation, and conclusion drawing. The results indicate that the culture of respect is the main foundation of adab education in Islamic boarding schools. The culture of respect is understood as respect for knowledge, teachers, and the educational process in the Islamic tradition. The culture of respect is formed through the process of habituation in daily life at the Islamic boarding school, the exemplary behavior of the Kyai and teachers, and the internalization of the value of respect within the students. Respectful practices such as minding one's speech, bowing when passing teachers, and maintaining one's posture during religious study sessions have developed into a social habit embedded in the lives of students. Research also shows that a culture of reverence plays a crucial role in the development of noble morals, such as humility, discipline, self-control, and respect for others. The research findings confirm that a culture of reverence is not a form of feudal relations, but rather a practice of adab education that shapes the moral and spiritual character of students through habituation, role models, and social experiences within the Islamic boarding school environment.